Pengujian dan Pengembangan Driving Cycle di Area Solo untuk Simulasi Kinerja Baterai Pack Kendaraan Listrik - Putra, Mufti Reza Aulia; Setiawan, Bagas; Arifwardana, Julian Fikri (Jurnal Teknik Mesin Indonesia, 2025)
Driving cycle testing is a crucial step in measuring the performance of battery electric vehicles (BEVs), especially in terms of energy efficiency and battery design optimization. This article discusses the driving cycle testing conducted in the Solo area, Central Java, to obtain a route that can be used in battery pack testing. The proposed driving cycle testing data shows good results, where the generated route pattern closely resembles the data in the model, with a difference of less than 3% between the field data and simulator data. The testing scheme using a 14.8 A load has met the applicable testing standards. Field test data recordings show an energy consumption value of 22.3 Ah, while simulation data shows a value of 22.8 Ah, with a difference of 2.2%. These recorded results provide consistent and relevant data to be used as input in electric vehicle simulators, allowing for more accurate simulations of battery performance under various real-world operational conditions. Therefore, this driving cycle data serves not only as a measure of vehicle efficiency but also as a valid basis for evaluating battery performance in simulator-based testing.